ANALISIS TEKNOLOGI TERHADAP PERTUMBUHAN EKONOMI DI ERA MODERN : Introduction, Research Method, Research Results and Discussion, Conclusion - Dika Anggraini Puspita; Sefti Lediya Devi; Setia Nisa; Heni Noviarita (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
Analyzing the tecnologi between economic growth in modern times is important for understanding complex economic dynamics. Economic growth reflects an increase in productive capacity and income, and economic structure describes the composition of sectors that contribute to the economy. In an ever-changing global context, the synergy between the two can be seen through increased productivity in key sectors such as technology, manufacturing and services. In modern times, technological innovation has become the main driver of economic growth. Sectors that adopt new technology tend to be more efficient and competitive. This not only encourages growth, but also changes the structure of the economy along with the emergence of new sectors and the transformation of old sectors. A diverse and balanced economic structure can support sustainable growth. If a country has a variety of sectors that complement each other, the risk of economic shocks can be minimized. Therefore, this synergy analysis is important for policy makers to develop strategies that not only encourage growth but also enable the economic structure to remain resilient and adaptable in the face of global change.